Impact of Pressure and Brine Salinity on Capillary Pressure-Water Saturation Relations in Geological CO2 Sequestration - Jongwon Jung; Jong Wan Hu (Advances in Condensed Matter Physics)
Capillary pressure-water saturation relations are required to explore the CO2/brine flows in deep saline aquifers including storage capacity, relative permeability of CO2/brine, and change to stiffness and volume. The study on capillary pressure-water saturation curves has been conducted through experimentation and theoretical models. The results show that as the pressure increases up to 12 MPa, (1) capillary pressure-water saturation curves shift to lower values at given water saturation, (2) after the drainage process, residual water saturation decreases, and (3) after the imbibition process, capillary CO2 trapping increases. Capillary pressure-water saturation curves above 12 MPa appear to be similar because of relatively constant contact angle and interfacial tension. Also, as brine salinity increases from 1 M to 3 M NaCl, (1) capillary pressure-water saturation curves shift to lower capillary pressure, (2) residual water saturation decreases, and (3) capillary CO2 trapping increases. The results show that pressure and brine salinity have an influence on the capillary pressure-water saturation curves. Also, the scaled capillary CO2 entry pressure considering contact angle and interfacial tension is inconsistent with atmospheric conditions due to the lack of wettability information. Better exploration of wettability alteration is required to predict capillary pressure-water saturation curves at various conditions that are relevant to geological CO2 sequestration.